Insider Research on Diversity and Inclusion: Methodological Considerations - Horváth, Zsuzsánna E. (Mednarodno inovativno poslovanje, 2018)
Workforce diversity management is fast becoming a significant component of in Multinational Corporations because it has outstanding benefits on inclusive workplace climate leading to improved work outcomes. The paper provides a conceptual background of the significance and implications of diversity management and inclusion, followed by a proposed insider research design. An employee perception focused approach is discussed that is believed to best capture the efficiency of diversity management and inclusion. Recommendations complement the conceptual framework and critical analyses.
Keywords: diversity management; inclusion management; insider research; methodology; metodologija; multinacionalne korporacije; multinational corporations; raziskovanje z osebno udeležbo; upravljanje inkluzivnosti; upravljanje raznolikosti